English Language Attrition of EFL Tertiary Students in China Over a Two-Month Break - Yu, Zhonggen (2011)
This study aims primarily to identify if participants experience attrition in speaking, speed and in-depth reading comprehension, short conversation and passage listening comprehension and writing abilities over a two-month holiday. Another research objective is to identify the attrition in vocabulary knowledge. Taking into consideration research practicability and efficiency, different numbers of participants took different tests. Three hundred and forty tertiary students from Nanjing University of Posts & Telecommunications (NUPT) were randomly selected to participate in the reading and listening tests before and after the holiday, 50 participants took part in the tests of writing, and 121 participated in the vocabulary tests. A questionnaire was administered to 340 tertiary students and it included numerous variables in relation to language attrition such as self-assessment of speaking skills, motivation and social activities. The data collected from the tests and questionnaire were analyzed via nonparametric and parametric tests using SPSS. Cranach’s alpha coefficient and MFRM (Multi Facets Rasch Model) were used to validate the reliabilities. The results of the tests indicated that participants’ short conversation listening comprehension scores gained significantly (p=.05) over the holiday period, showing improvement. However, no statistical significance was found in the passage listening comprehension scores, thus indicating no presence of significant attrition or improvement. In addition, the results did not indicate any statistically significant attrition in both modes of reading comprehension though a slight increase was found in speed reading comprehension scores and evidence of slight attrition was obtained in in-depth reading comprehension. No significant gender differences were found in speed and in-depth reading, short conversation listening and passage listening conversation scores. The results also showed that participants experienced a statistically significant level of attrition in not only overall writing skills but also specific writing skills such as pertinence, coherence, clarity and grammar over the holiday period. Females suffered a higher level of attrition than males in all tested specific writing skills except for grammar. Significant attrition was also found in vocabulary knowledge. The results of the questionnaire showed that participants believed that their overall English proficiency (including speaking skills) attrited over the holiday period although the listening and reading test results did not reveal any statistically significant attrition. Participants showed a lower level of positive motivation and fewer social activities for studying English language during the holiday than before the holiday and this could have contributed to the attrition in some of the linguistic abilities. The findings suggested that attrition was not an overall phenomenon affecting all language skills. Thus, it might point to students having different threshold levels in learning and maintaining the language skills learnt. Institutions would need to initiate measures that address attrition in order that the problem be minimized. A low level of attrition would lead to graduates having a better language ability to serve the China economy that is fast expanding. More proficient graduates in English would help to realize the economic goals and to participate more efficiently both locally and globally.